Optimized Biotransformation of Icariin into Icariside II by β-Glucosidase from Trichoderma viride Using Central Composite Design Method - Cheng, Tao (Biomed Res Int, 2016)
A crude β-glucosidase has been produced from Trichoderma viride and used to explore a simple method to prepare icariside II from icariin. The crude enzyme has been studied by zymography method and used for hydrolysis of ICA. To achieve a high conversion rate of ICA, various factors have been studied including pH, reaction time, temperature, initial concentration of enzyme, and initial concentration of ICA through central composite design experiments. In the condition of the optimum hydrolysis parameters with pH 4.0, 41°C, 1.0 mg/mL ICA, and 9.8 U/mL crude β-glucosidase, the conversion rate of ICA reached 95.03% at 1 h. Moreover, the cytotoxicity test showed that ICA II performed inhibition effects on proliferation of A549 cell, while ICA has no cytotoxicity. It indicated that the hydrolysis transformation study of ICA is valuable for exploration of active new drugs.